CSS : the definitive guide : web layout and presentation - Meyer, Eric A.; Weyl, Estelle (O'Reilly Media, 2023)
If you're a web designer or app developer interested in sophisticated page styling, improved accessibility, and less time and effort expended, this book is for you. This revised fifth edition provides a comprehensive guide to CSS implementation along with a thorough review of the latest CSS specifications. Authors Eric Meyer and Estelle Weyl show you how to improve user experience, speed development, avoid potential bugs, and add life and depth to your applications through layout, transitions and animations, borders, backgrounds, text properties, and many other tools and techniques. We read the specs so you don't have to! This guide covers: Selectors, specificity, and the cascade, including information on the new cascade layers New and old CSS values and units, including CSS variables and ways to size based on viewports Details on font technology and ways to use any available font variants Text styling, from basic decoration to changing the entire writing mode Padding, borders, outlines, and margins, now discussed in terms of the new block- and inline-direction layout paradigm used by modern browsers Colors, backgrounds, and gradients, including the conic gradients Accessible data tables Flexible box and grid layout systems, including new subgrid capabilities 2D and 3D transforms, transitions, and animation Filters, blending, clipping, and masking Media, feature, and container queries.